Tracking free water in human body by magnetic resonance imaging: new insights on the network pathways - Lu Sun; Liting Wang; Le He; Changsong Liu; Fengshan Bai (Royal Society Open Science)
Water is the most indispensable material for life. Although extensive research has been carried out at the microscopic level, including studies focusing on transport and molecular effects, the macroscopic water system of the human body is still unclear. In this study, the distribution of free water in the human body under natural conditions was non-invasively depicted by magnetic resonance hydrography sequences. Spatial saturation technique was used to explore the dynamic properties of free water. Imaging and post-processing results reveal that abundant free water formed a macroscopic network consisting of interconnected pathways. The slow flow trajectories of some waterways were captured in the saturation band. The free-water channels enclosed or bordered the space around blood vessels and nerves or traversed the tissues. This spatial relationship is similar to the fluid flow patterns in the interstitial space in the periphery and the glymphatic system of the brain, suggesting potential physiological functions and pathological variations.